2021
DOI: 10.1038/s41598-021-98036-2
|View full text |Cite
|
Sign up to set email alerts
|

Wuzi-Yanzong prescription alleviates spermatogenesis disorder induced by heat stress dependent on Akt, NF-κB signaling pathway

Abstract: Akt and nuclear factor kappa B (NF-κB) signaling pathways are involved in germ cell apoptosis and inflammation after testicular heat stress (THS). We observed that after THS induced by the exposure of rat testes to 43 °C for 20 min, their weight decreased, the fraction of apoptotic testicular germ cells significantly increased, and the proliferation of germ cells was inhibited. In addition, THS lowered serum testosterone (T) level, whereas the levels of follicle stimulating hormone and luteinizing hormone were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Testicular heat stress lowered serum testosterone levels, whereas the levels of follicle-stimulating hormone and luteinizing hormone were not significantly changed. The ultrastructure of the seminiferous tubules became abnormal after testicular heat stress, the structure of the blood–testis barrier became loose, and the Sertoli cells showed a trend of differentiation [ 48 ]. Heat stress decreased epithelial thickness, the loosening and vacuolization of the germinal epithelium, the presence of cellular debris in the lumen, and the appearance of multinucleated giant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular heat stress lowered serum testosterone levels, whereas the levels of follicle-stimulating hormone and luteinizing hormone were not significantly changed. The ultrastructure of the seminiferous tubules became abnormal after testicular heat stress, the structure of the blood–testis barrier became loose, and the Sertoli cells showed a trend of differentiation [ 48 ]. Heat stress decreased epithelial thickness, the loosening and vacuolization of the germinal epithelium, the presence of cellular debris in the lumen, and the appearance of multinucleated giant cells.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between germ cell proliferation and apoptosis is critical for spermatogenesis. It has previously been shown that heat‐stress or testicular hyperthermia decreases germ cell proliferation and induces apoptosis in the testis (Kanter et al, 2013; Hu et al, 2021; Hasani et al, 2020; Eslami Farsani et al, 2022). Our data are in agreement with a previous study, where it has been shown that heat stress induces apoptosis by stimulating active caspase3 expression, decreasing the survival factor Bcl2 (Vera et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This regulation, in turn, is achieved through the effect of WZYZP on the levels of T, AR, erythropoietin (EPO), and Tyro-3, Axl, and Mer receptors. [60] Li [66] found that WZYZP could stimulate the proliferation of juvenile rat testis-supporting cells by activating the PI3K/Akt signaling pathway and prompting Akt phosphorylation. Chen et al [49] showed that WZYZP suppressed TGF-β expression and activated the PI3K/Akt/mTOR signaling pathway, thereby promoting germ cell proliferation and inhibiting germ cell apoptosis and autophagy.…”
Section: Modulatory Effects On Signaling Pathwaysmentioning
confidence: 99%
“…Chen et al [49] showed that WZYZP suppressed TGF-β expression and activated the PI3K/Akt/mTOR signaling pathway, thereby promoting germ cell proliferation and inhibiting germ cell apoptosis and autophagy. Hu et al [60] affirmed that WZYZP could restore BTB structural function, inhibit inflammatory factor expression, and reduce tissue cell damage in testicular inflammatory rats by blocking the TLR/MyD88/NF-κB pathway. Yang et al [54] illustrated that WZYZP regulated testicular spermatogenesis in rats with oligoasthenozoospermia through the TGF-β1/ Smads signaling pathway.…”
Section: Modulatory Effects On Signaling Pathwaysmentioning
confidence: 99%